Vascular tracheobronchial compression syndrome secondary to contained ruptured thoracic aortic aneurysm. Issue 5 (17th May 2021) - Dinh, Krystal; Manuel, Lucy; Somers, Miles; Vicaretti, Mauro
Abstract: Vascular tracheobronchial compression syndrome is the compression of the trachea or pulmonary bronchus by a vascular structure. It is primarily a diagnosis in children and secondary to congenital vascular anomalies. In adults, vascular tracheobronchial compression syndrome can be either congenital or required with a vast majority of congenital conditions found incidentally on imaging. Acquired conditions are largely due to aortic arch aneurysms or kinking of the aorta. The case described herein illustrates the rare case of a saccular thoracic aneurysm causing compression of the left primary bronchus. Patients may have a history of gradual onset of symptoms involving both the airway and oesophagus. Vascular tracheobronchial compression syndrome may go undetected and asymptomatic throughout an individual's lifespan, however as described herein this syndrome may also be life-threatening.